Implementation of the Viola-Jones Algorithm for a Hand Sign Language Translation System - Novianti, Atik; Muthiah, Siti Nurul; Mulyana, Asep (Universitas Muhammadiyah Surakarta, 2024)
People who speech impaired that uses body movements to deliver information. In everyday life, it is not uncommon for people with disabilities to communicate with normal people who do not understand the meaning of what is delivered. One example is when a speech-impaired person wants to order food at drive-thru service fast food restaurant, the seller must have special skills to understand what is being delivered. In this paper, we will discuss the application of the Viola Jones algorithm for hand gesture detection systems in drive-thru service fast food restaurant. The Viola Jones algorithm was proposed because the algorithm is the most famous and best choice of gesture classifier for detecting hands in real time based on the accuracy speed. The system is able to translate the given gestures, data enters Firebase as a real time database, sellers can find out the total shopping through the cashier application. The system cannot translate the gesture if the given hand is not completely in the specified area of the box. Based on testing on 10 different respondents, the system can detect hand gesture with an average system success of 92,01%.